(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aimed to examine how socio-economic structures shape Mrs. Bennet’s psychological disposition and social behavior in Pride and Prejudice (1813). The analysis drew on Marxist literary criticism as its primary framework, supported by Bourdieu’s concept of habitus, to investigate how material conditions produce class anxiety as both a psychological and behavioral phenomenon. The results showed that Mrs. Bennet’s behavior is not a matter of personal character but a direct response to the material conditions that govern her existence. Her nervous temperament, obsessive concern with her daughters’ marriages, need for social recognition, and fear of downward mobility reflect the internalized pressures of a class position that is economically precarious and socially uncertain. These findings suggest that class anxiety, as experienced by Mrs. Bennet, is a product of structural inequality rather than individual failing, revealing how deeply material conditions shape the way individuals think, feel, and act in Austen’s depiction of Regency-era England.